ISTANBUL’S THIRD AIRPORT IN TERMS OF TRANSPORTATION GEOGRAPHY: GEOPOLITICS, REGIONAL AND ECONOMIC EFFECTS - KAHRAMAN, Cengiz; ALKAN, Güler (PEOPLE: International Journal of Social Sciences, 2018)
More passengers have come to use airplanes in parallel with the developing aircraft technology. The remarkable and rapid development of commercial airlines after the World War II positively affected the costs to turn airborne transportation into a global activity taken up by masses. Doubtlessly, immense is the effect of developing airborne transportation on the emergence and dissemination of “globalization” herein.As one of the major components of airborne transportation, airports serve as spaces allowing for direct and connecting flights in a short time and make considerable contributions to the economy of the country they are located in. A region’s airborne accessibility enables the transportation of any goods and services to that particular region in a short while. Thus, accessibility is indispensable to the growth of a region’s economy. Taking the abovementioned as a premise, some airports have acquired new functions not only to regulate ordinary flight services and airborne transportation but also to turn into hubs to orchestrate interregional transportation. Such airports also function as tourism embassies. Among the hubs are the airports in Dubai, Bangkok, Frankfurt, London, Paris, and New York. In recent years, Istanbul has set out to be listed among the above hubs thanks to its geographical location and developing economy. Istanbul’s Third Airport, which has reached almost 70% of its construction and will come into service soon, has been designed to be the largest airport of the world. Istanbul is distinguished from the metropolitans listed above for the historical role it played and the diversity of its historical and cultural landmarks. Throughout its history of around 8000 years, Istanbul has served as a capital to the Roman, Byzantine, and Ottoman Empires, which exerted substantial influences on the world history, and is teemed with cultural heritage of these civilizations. Every year, the city hosts some 12 million tourists. The present study discusses the probable global effects of Istanbul’s Third Airport under construction in terms of transportation geography and its geopolitical, regional, and economic effects in consideration of its projected mission.